Penerapan Model Pembeljaran Problem Based Learning Ditinjau dari Gaya Belajar Peserta Didik untuk Meningkatkan Hasil Belajar Kognitif - Nurrohmah, Siti; Sulianto, Joko; Khasanah, Rohmah; Prayito, M. (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to improve students' cognitive learning outcomes by applying the Problem Based Learning (PBL) learning model in terms of their learning styles. The research was conducted at SDN Palebon 02 Semarang with the research subjects being 27 class 4-B students. The research method used is Classroom Action Research with two cycles, each consisting of planning, implementation, observation and reflection. The research results show that the application of PBL which is adapted to students' visual, auditory and kinesthetic learning styles has succeeded in improving their learning outcomes. In cycle I, the average student score was 58, while in cycle II it increased to 84. This shows a significant increase in understanding and application of Indonesian language material. In conclusion, the PBL model which is used by considering students' learning styles can be effective in improving cognitive learning outcomes. The implication of this research is the importance of adapting learning methods according to the individual needs of students to improve the quality of learning in schools.